The Effect of Clitoria Ternatea's Drink on Insomnia in Post COVID-19 Patients - Solihati Solihati; Nurry Ayuningtyas Kusumastuti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The COVID-19 pandemic evokes an effect on patients of post-COVID-19. One of them is diminished sleep quality known as insomnia. Concerning the problem, WHO strongly supports the supportive supplementary medicines made from traditional plants during the COVID-19 pandemic, one of which is by utilizing butterfly pea flowers. The study aimed to determine the effect of butterfly pea flower drinks on insomnia in post-COVID-19 patientsSubjects and Method: This was a randomized controlled trial. The population in this study was 36 respondents who experienced insomnia post-COVID-19. The sampling technique used was simple random sampling. The total sample of 32 respondents was divided into 2 groups, namely 16 respondents as an intervention group and 16 respondents as a control group. This research was conducted for 14 days, from September 18 to October 3, 2022, at the Islamic Housing Complex, Neighborhood Unit 001, Kelapa Dua, Tangerang Regency. The independent variable in this study was the administration of butterfly pea flower drink and the dependent variable was insomnia. The study instruments used were observation sheets for the administration of butterfly pea flower drink and the Insomnia Rating Scale (IRS) questionnaire for the insomnia variable. The study used an independent t-test for data analysis.Results: Independent t-test results indicated that the intervention group (Mean= - 4.31 SD= 3.70) was lower than the control group (Mean= -0.38; SD= 2.50), and the result was statistically significant (p= 0.001).Conclusion: There is an effect of butterfly pea flower drink on insomnia in post-COVID-19 patients. Keywords: butterfly pea flower, post-COVID-19, insomnia, healthy drink.Correspondence:Solihati. Yatsi Madani University. Jsl. Aria Santika No.40A, RT.005/RW.011, Margasari, Kec. Karawaci, Kota Tangerang, Banten 15114. Email: solyan8000@gmail.com. Mobile: +6281288863088.Journal of Health Promotion and Behavior (2023), 08(01): 13-21DOI: https://doi.org/10.26911/thejhpb.2023.08.01.03